High pressure/temperature pasting and gelling of starch related to multilevel structure-analyzed with RVA 4800. (1st November 2022) - Tian, Yu; Qu, Jianzhou; Zhou, Qi; Ding, Li; Cui, Ying; Blennow, Andreas; Zhong, Yuyue; Liu, Xingxun
Abstract: This paper evaluated the relationship between multi-scale structure and high-pressure gelation properties of nine types of starches with different amylose (AM) content and crystalline polymorphic structure by RVA 4800. Higher average chain lengths of long amylopectin (AP) chains (DP > 36) and AM content, and lower relative content of short AP chains (DP ≤ 36) contributed to the higher peak temperature and peak time at 95–140 °C, and lower peak viscosity, through viscosity, and final viscosity at 95–110 °C. Rheological and texture parameters including storage modulus, loss modulus, hardness, and gumminess, had no significant correlation with starch structural parameters at 95–120 °C, but were instead controlled by AM molecular structure at 130–140 °C. AM content was mainly responsible for the rheological behaviors of starch gels at 130–140 °C, and short and intermediate AM chains were mainly associated with the texture of starch gels at the temperature ranges. Graphical abstract: Unlabelled Image Highlights: Significant relationships between starch multi-scale structure and high-pressure gelation were identified. Higher amylose content contributed to higher peak temperature and peak time. High amylose content resulted in low peak and final viscosities. Amylose fine structure significantly correlated with rheological and texture properties at high temperature.